Gender-Based Justice in Matrimonial Property Law: A Comparative Study of Post Divorce Protection for Women in Indonesia and Thailand - Veronica Khosasi Tarigan; Atikah Rahmi (PALAR | PAKUAN LAW REVIEW, 2026)
The division of marital property after divorce has become a crucial issue that often disadvantages women due to structural inequalities and patriarchal cultural influences. This study aims to analyze the legal regulation of marital property division in Indonesia and Thailand from a gender-based justice perspective, as well as to evaluate the effectiveness of legal protection for women’s economic rights after divorce. This research employs a normative juridical method with a comparative approach to examine the regulations of both countries. The primary legal materials include Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law, the Civil and Commercial Code of Thailand, and the Gender Equality Act of Thailand. The findings indicate that Indonesia adopts the principle of joint marital property (gono-gini) with an equal distribution system (50:50), as stipulated in Article 37 of the Marriage Law and Article 97 of the Compilation of Islamic Law. While this system provides legal certainty, it tends to be rigid and insufficiently accommodates women’s non-economic contributions within the household. In contrast, Thailand applies the concept of sin somros (marital property) with an equitable distribution system that is more flexible, taking into account the actual contributions of each party, including women’s domestic roles. From a gender justice perspective, Indonesia’s equal distribution system appears formally fair but fails to reflect substantive justice, whereas Thailand’s system is more responsive, although it relies on judicial discretion. The effectiveness of legal protection in Indonesia is hindered by patriarchal culture, limited access to justice, and inconsistent court decisions, while Thailand demonstrates a more progressive legal framework. This study recommends the reconstruction of Indonesia’s joint property system by maintaining equal distribution as the default rule while allowing greater judicial flexibility to consider substantive contributions and the post-divorce economic conditions of women.   Keywords: Gender Justice, Marital Property, Divorce, Legal Protection